On the road to SME sector development in Bangladesh: a guideline based on current challenges and opportunities - Rahman, Syed Abidur; Ahmad, Noor Hazlina; Taghizadeh, Seyedeh Khadijeh (IGI Global, 2017)
Entrepreneurship has been deliberated as multidimensional and multidisciplinary study.From the economic point of view entrepreneurship is the central force for economic development for any nation.Scholars and policy makers now have started to see entrepreneurship as panacea for inclusive growth. Entrepreneurships are most widely popular and discussed area.Study on small and medium sized enterprises (SMEs) has been maturing for the last decade as it has been regarded as significant player for the social development along with the economic development.In Bangladesh, SMEs account for a large proportion of the total establishments in various sectors.Considering the importance of the SME sector in Bangladesh, this study intends to explore and sketch-out the landscape of current SME setting in Bangladesh.With this aim the study has extensively carried out literature review, observed and understood the secondary data obtained from various organizations, and finally presented a policy driven recommendation (micro and macro level) which would enable to develop the SME sector in a developing country like Bangladesh.